Digital Pedagogical Transformation and Teacher Work Engagement in Secondary Schools - Noraini Idris; Ghavifekr Simin; Hairul Nizam Ismail (Generasi Sains Indonesia, 2026)
This study investigates the impact of digital pedagogical transformation on teacher work engagement among secondary school teachers in Selangor, Malaysia. Grounded in the Job Demands–Resources (JD-R) model, the study aims to examine how digital-related job demands and job resources influence teachers’ levels of vigor, dedication, and absorption. A quantitative research design was employed using a cross-sectional survey of 320 teachers, and the data were analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that digital job resources have a strong positive effect on teacher work engagement, while digital job demands have a significant negative effect. However, the influence of resources is more dominant, suggesting that supportive conditions can mitigate the adverse effects of digital workload and complexity. These results demonstrate that digital transformation operates as a dual mechanism, acting both as an enabler and a constraint depending on contextual factors. The novelty of this study lies in its integrative approach, conceptualizing digital pedagogical transformation as a multidimensional construct within the JD-R framework. The study contributes to theory by extending the application of the JD-R model in digital education contexts and provides practical implications for policymakers to design balanced strategies that enhance teacher support. The findings highlight the importance of prioritizing teacher-centered approaches in achieving sustainable digital transformation in education.